2022
DOI: 10.1253/circj.cj-21-0965
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience of Tafamidis Treatment in Japanese Patients With Wild-Type Transthyretin Cardiac Amyloidosis From the Kochi Amyloidosis Cohort

Abstract: Background: Tafamidis has emerged as an effective treatment for patients with wild-type transthyretin cardiac amyloidosis (ATTRwt CA). The early experience of tafamidis treatment for Japanese patients with ATTRwt CA is reported here. Methods and Results:Over the past 2 years, in 82 patients with ATTRwt CA (mean age of 81.7±6.0 years), tafamidis treatment was initiated for 38 patients. The remaining 44 patients were not administered tafamidis. The most frequent reason for non-administration of tafamidis was adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Ochi et al 17 . reported the early experience of tafamidis in patients with ATTRwt‐CM in Kochi University ( n = 38).…”
Section: Discussionmentioning
confidence: 99%
“…Ochi et al 17 . reported the early experience of tafamidis in patients with ATTRwt‐CM in Kochi University ( n = 38).…”
Section: Discussionmentioning
confidence: 99%
“…Tafamidis showed a decrease in CV mortality due to heart failure in the study by Ochi et al ., while in the ATTR-ACT trial, it did not exhibit any reduction 6 , 8 . However, according to the fixed effect model, the comprehensive results from the forest plot appeared to give a remarkable reduction in CV mortality with an overall effect estimate (OR 0.72; 95% CI: [0.56–0.92], P =0.009, I 2 =88%; Fig.…”
Section: Resultsmentioning
confidence: 74%
“…1 . 1 ) 6 , 8 . To better characterize this outcome, a subgroup analysis was conducted for CV mortality due to heart failure (OR 0.89; 95% CI: [0.63–1.25], P =0.50, I 2 =93%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we consider patient selection before treatment initiation to be an important point for treatment efficacy. Regarding the administration of tafamidis, Ochi, et al 19) emphasized the importance of patient selection and confirmed that the disease should not be advanced in patients. Our patients may have been in the advanced stages of ATTR-CM and frailty, which may have diminished the effect of tafamidis.…”
Section: Discussionmentioning
confidence: 99%